KOMPLEKS SANLARDÍŃ ELEKTROTEXNIKALÍQ MÁSELELERDI SHESHIWDE QOLLANÍWÍ - Kutlımuratov, B.; Xalknazarov, A. (SCIENCE and SOCIETY, 2024)
This article describes the use of complex numbers and Fourier series for solving electrical problems.